Modulation of smoking cue reactivity by social context—Implications for exposure therapy in virtual reality - Winkler, Markus H.; Li, Yonghui; Pauli, Paul; Mühlberger, Andreas (Frontiers in Virtual Reality, 2023)
Rationale: Social factors are considered as important for the initiation and maintenance of drug abuse. Virtual reality (VR) research on cue-reactivity and exposure frequently incorporates social stimuli as part of complex drug-intake scenarios. Only rarely attempts are made to dissect the im-pact of the different components and their interactive effects. The present study critically extends this line of research by investigating modulatory effects of social context on the reactivity evoked by proximal smoking cues. Methods: Thirty-two smokers and 33 never smokers were presented in VR with proximal cues and neutral stimuli, embedded in a social context or a neutral context. A virtual hand model was used to translate real hand movements into VR. Each trial started with the presentation of the different stimulus-context combinations. Discrete stimuli were presented on the table in front of the partici-pants and contextual stimuli at the end of the table. Afterwards, participants were instructed to grasp the target stimulus (cigarette vs. pencil) in front of them. After successful contact, the stimu-lus appeared in the virtual hand. Modulation of cue reactivity by social context was assessed by self-report, physiological measures, and overt approach behavior. Results: The results revealed modulatory effects of social context on the responses to proximal smoking cues in smokers. In contrast to never smokers, smoking cues evoked craving in smokers, which was attenuated in a social context. Furthermore, social context increased the latency to ap-proach and contact the cigarette in the group of smokers but did not affect behavioral approach re-sponses in never smokers. Other data provided indications for interactive, but also main effects of cues and contexts. Interestingly, cue-evoked craving was increased after contact with the virtual cigarette. Conclusions: The present study critically extends previous research by providing evidence for the modulation of cue-reactivity by social context. The results are particularly important given the well-established role of drug-associated environmental contexts in the stimulus control of addictive behaviors. Our results emphasize the need to address social context effects on cue-reactivity in basic research and treatment and further suggest that changes in the perceived availability of smok-ing might enhance or inhibit cue-evoked reactivity.